The positive association between internal migration and hospitalization among the older adults in China: Regional heterogeneity and chronic disease management - Huixiang Zhong; Huixiang Zhong; Jin Yang; Na Zhao; Xu Li; Yanli Zhang (Frontiers Media S.A., 2022)
BackgroundPost-retirement migrants are rapidly increasing in China, but the impact of internal migration on hospitalization among older adults remains under-researched. Understanding this impact is essential for health policies development and improvement. This study aims to identify the most vulnerable population, evaluate the association between migration and hospitalization, and discuss potential causes of the association.Methods14,478 older adults were extracted from the 2018 to 2019 Chinese Longitudinal Healthy Longevity Survey (CLHLS) database and divided into four groups according to migration experience and age at migration: non-migrants, pre-adulthood migrants, pre-retirement migrants, and post-retirement migrants. Post-retirement migrants were key research subjects. We employed Pearson's chi-square test to compare group differences in outcome and covariates, and multivariate logistic regression analysis to examine the association between migration and hospitalization by regions and chronic conditions.ResultsSignificant intergroup differences were observed in demographic characteristics, socioeconomic factors, health habits, and health-related factors. Post-retirement migrants displayed following characteristics: female predominance (61.6%; 1,472/2,391), tending toward urban areas (80.9%; 1,935/2,391), and the highest prevalence rate of chronic disease (46.7%; 1,116/2,391). Urban migrants in eastern China were more likely to be hospitalized (OR = 1.65; 95% CI: 1.27-2.15), especially those who were diagnosed with chronic disease (OR = 1.51; 95% CI: 1.04-2.19) or with unconfirmed chronic conditions (OR = 1.98; 95% CI: 1.36-2.89).ConclusionsInternal migration is associated with the hospitalization of post-retirement migrants moving to eastern China. Improved chronic disease management and early interventions might lower the hospitalization. Effective policies should be formulated to reduce the disparity in primary care services across China, thereby facilitating the access of migrants to these services.